PEMANFAATAN PUPUK HAYATI PADA TANAMAN JAGUNG MANIS UNTUK MENINGKATKAN PENDAPATAN USAHA TANI DI LAHAN RAWA LEBAK - Mahdiannoor Mahdiannoor; Nurul Istiqomah; Purna Kusumayana (Universitas Islam kalimantan MAB, 2018)
Problems faced by Mawar Farmers Group Mawar Sari Village and Farmers Group Ingin Maju Pasar Senin Village Amuntai Tengah Sub-District Hulu Sungai Utara Regency South Kalimantan Province is; farmers do not use fertilizer for corn crops, because their assumption that the swamp land lebak fertile enough, the lack of interest of farmers using superior varieties for corn crops and farmers do not have knowledge about good corn cultivation technology in swamp land. From these various problems, we are given solution with counseling and dissemination about introduction and dissemination of the use of biological fertilizer, sweet corn varieties for the land, good corn cultivation technology in swamp land and make demplot of sweet corn plantation with the use of biofertilizer in Pasar Senin Village for convincing and providing concrete evidence to both partners PKM that the use of biological fertilizers is not inferior to the use of chemical fertilizers in corn crops with maximum results. The results of analysis of corn farming after the activity took place the average R / C ratio in the Pasar Senin Village and Mawar Sari Village experienced a decrease caused by several things.